2014
DOI: 10.1111/jth.12534
|View full text |Cite
|
Sign up to set email alerts
|

The fibrinogen γA/γ′ isoform does not promote acute arterial thrombosis in mice

Abstract: Background Elevated plasma fibrinogen associates with arterial thrombosis in humans and promotes thrombosis in mice by increasing fibrin formation and thrombus fibrin content. Fibrinogen is composed of six polypeptide chains: (Aα, Bβ, and γ)2. Alternative splicing of the γ chain leads to a dominant form (γA/γA) and a minor species (γA/γ’). Epidemiologic studies have detected elevated γA/γ’ fibrinogen in patients with arterial thrombosis, suggesting this isoform promotes thrombosis. However, in vitro data show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…γ′-Fibrinogens result in the formation of thinner fibers with increased branching [24]. Epidemiologic data initially indicated that γ′-fibrinogen isoforms were elevated in patients with arterial thrombosis, but more recently both human and murine models suggest a relative antithrombotic role for γA/γ′, possibly as a result of thrombin sequestration [25,26]. Thrombus formation depends upon not only the total fibrinogen concentration, but also the isoform composition of the fibrinogen pool.…”
Section: Fibrin Formation and Clot Structurementioning
confidence: 99%
See 1 more Smart Citation
“…γ′-Fibrinogens result in the formation of thinner fibers with increased branching [24]. Epidemiologic data initially indicated that γ′-fibrinogen isoforms were elevated in patients with arterial thrombosis, but more recently both human and murine models suggest a relative antithrombotic role for γA/γ′, possibly as a result of thrombin sequestration [25,26]. Thrombus formation depends upon not only the total fibrinogen concentration, but also the isoform composition of the fibrinogen pool.…”
Section: Fibrin Formation and Clot Structurementioning
confidence: 99%
“…This paradox may be explained by a sequestration effect, whereby, under normal conditions, thrombin is sequestered by binding to fibrinogen. In patients with afibrinogenemia, there may be greater availability of active thrombin from a lack of fibrinogen binding, resulting in a prothrombotic tendency upon exposure to exogenous fibrin [26,98]. This theory may explain reports of afibrinogenemia patients who develop thrombosis when receiving fibrinogen concentrates [99101].…”
Section: Lessons From Hemophilia and Inherited Disorders Of Fibrinmentioning
confidence: 99%
“…Fibrinogen decreased the residual ETP, not only by decreasing the ETP 1APC , but also by increasing the ETP 2APC . The ability of fibrinogen to increase the ETP determined at high TF in the absence of APC is a well-known effect, which has been attributed to the fact that fibrin(ogen) binds thrombin and delays its inhibition by a 2 -macroglobulin and antithrombin, [27][28][29][30] without affecting its ability to convert the fluorogenic substrate. The observation that gA/g9 fibrinogen binds more thrombin with a higher affinity 29 compared with gA/gA fibrinogen, can explain why this fibrinogen isoform is more effective than gA/gA fibrinogen in increasing the ETP 2APC .…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with published data and is probably due to the ability of fibrinogen to protect thrombin from inhibition by antithrombin and a 2 -macroglobulin. [27][28][29][30] However, the addition of APC decreased thrombin generation relatively more in whole plasma, resulting in lower ETPs in whole plasma than in defibrinated plasma at each APC concentration (Figure 2). At the highest APC concentration the ETP was almost 10 times (normal plasma) and .3 times (FV Leiden heterozygous plasma) lower in whole than in defibrinated plasma.…”
Section: Effect Of Fgg H2 Haplotype On Apc Resistance In Fv Leiden Camentioning
confidence: 99%
“…Rather, ' fibrinogen concentrations seem to reflect general inflammation that accompanies and may contribute to atherosclerotic CVD, instead of ' fibrinogen being a causal risk factor 12 . In addition to this, Walton et al found that elevated levels of A A fibrinogen promoted arterial thrombosis in vivo, whereas A ' fibrinogen did not 13 . Nevertheless, as ' chain modulates clot formation in vitro, further studies are required to elucidate its functional properties and its possible relationship with bleeding disorders or thrombosis.…”
Section: Introductionmentioning
confidence: 99%